Efficacy and safety of apixaban in a patient with systemic venous thromboembolism associated with hereditary antithrombin deficiency. Issue 3 (March 2019) - Nojima, Yuhei; Ihara, Madoka; Adachi, Hidenori; Kurimoto, Tetsuya; Nanto, Shinsuke
Abstract: A 40-year-old man with progressively worsening dyspnea was admitted to our hospital. On physical examination, pulse oximetry results demonstrated 80% oxygen saturation in room air. The lungs sounded clear, and both extremities appeared normal, without pitting edema. His echocardiography revealed a pressure overload in the right ventricle. Suspecting the presence of pulmonary thromboembolism, we performed an enhanced computed tomography (CT). CT results revealed systemic venous thromboembolism (VTE) involving the superior mesenteric vein, inferior vena cava (IVC), right common iliac vein and pulmonary arteries, as well as splenomegaly and edema of the small intestine with ascites. After insertion of a retrievable IVC filter, we prescribed 10 mg of apixaban twice daily for the first 7 days, followed by 5 mg twice daily as long-term therapy. Confirming no exacerbation of the VTE symptoms, we removed the IVC filter 14 days after admission. Additionally, hereditary antithrombin deficiency was unraveled as the etiology of systemic VTE. Although an enhanced CT at 6 months follow-up showed that almost all previous VTE had dissolved, we decided to prescribe apixaban indefinitely. Fortunately, he has not experienced a recurrence of VTE or any bleeding events to date. <Learning objective: Hereditary antithrombin (AT) deficiency is a thrombophilia, which has a high potential to develop venous thromboembolism (VTE). Direct oral anticoagulant (DOAC) therapy can substitute for conventional therapy, including parenteral anticoagulant plus warfarin. However, the efficacy and safety of DOAC treatments for patients with hereditary AT deficiency with systemic VTE have not yet been clarified. This report highlights the efficacy of a single apixaban prescription in achieving excellent outcomes in resolving systemic VTE with no bleeding events.>